Expanded Role of the Operating Room Nurse In The Perioperative Practice Setting - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 1993)
The project was initiated in response to a mandate from the ORNAC Strategic Planning session of April, 1992 to investigate “The Expanded Role of the Operating Room Nurse and to set up the future direction for perioperative nursing”.